1955
DOI: 10.1103/physrev.98.217
|View full text |Cite
|
Sign up to set email alerts
|

Electron Scattering from the Proton

Abstract: In Eqs. (4), (6), and (8)-(11) we have neglected relativistic corrections. For tt=sr/2 the relations (2) and (9) vanish whereas (10) and (11) become identical. There remain therefore six independent relations between the coeKcients b(sr/2)=c(sr/2), d(sr/2), and e(sr/2), i.e. , between five real parameters which determine the transition matrix T(sr/2, «b) except for an absolute phase factor. For angles 0&t7&sr/2, one can obtain eleven relations for nine parameters. The experimental quantities are of course not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
165
0
3

Year Published

1957
1957
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(177 citation statements)
references
References 3 publications
5
165
0
3
Order By: Relevance
“…Quite early the interest turned to the nucleon; the first FF measurements of the proton were reported in 1955 [Hof55], and the first measurement of the neutron magnetic FF was reported by Yearian and Hofstadter [Yea58] in 1958. Simultaneously much theoretical work was expanded to the development of models of the nucleus, as well as the interaction of the electromagnetic probe with nuclei and the nucleon.…”
Section: Introductionmentioning
confidence: 99%
“…Quite early the interest turned to the nucleon; the first FF measurements of the proton were reported in 1955 [Hof55], and the first measurement of the neutron magnetic FF was reported by Yearian and Hofstadter [Yea58] in 1958. Simultaneously much theoretical work was expanded to the development of models of the nucleus, as well as the interaction of the electromagnetic probe with nuclei and the nucleon.…”
Section: Introductionmentioning
confidence: 99%
“…Early experiments revealed that the proton is a composite particle [4,5,6,7]: i.e. non-zero Pauli and Dirac mean-squared radii and anomalous magnetic moments were measured among other observables.…”
Section: Introductionmentioning
confidence: 99%
“…In the nonrelativistic approximation, the nucleon form factors are Fourier transforms of the charge and current distributions in the proton [3]. Another broad part of these experiments have been devoted to deep inelastic scattering (DIS), to study the PDFs.…”
Section: Phenomenology Of Pion Electroproductionmentioning
confidence: 99%